Pendidikan Islam dan Fenomena Radikalisme Agama - Abdul Kholik (Jurnal Kependidikan, 2017)
Religious radicalism is a great theme in society. This theme is not only present in industrial society, but also in agrarian society, farmers, and even intellectuals. The phenomenon of radicalism is a problem that needs to find a way out because it is massive and difficult to control. The role of the state in tackling radicalism can be done through welfare, and protecting all citizens regardless of race, race, and religion. However, the thing that happens in society is that the rich get richer and the poorer the poorer, which can lead to the emergence of radicalism. Some of the strategies in responding to the emergence of radicalism include: The use of military channels, the use of counter arguments, improving welfare by making improvements in the social, economic, political and cultural fields, counter-use of violence / insurrection by spreading the idea of ​​world peace.